Photocatalytic degradation of triclocarban in aqueous solution using a modified zeolite/TiO2 composite: kinetic, mechanism study and toxicity assessment - Arifin, Siti Nor Hidayah; Radin Mohamed, Radin Maya Saphira; Adel Al-Gheethi, Adel Al-Gheethi; Chin Wei Lai, Chin Wei Lai; Yashni Gopalakrishnan, Yashni Gopalakrishnan; Hairuddin, Nur Diyana; Dai-Viet Vo, Dai-Viet Vo (2023)
The current work aimed to investigate the degradation of the triclocarban (TCC) in aqueous solution using a modified zeolite/ TiO2 composite (MZTC) synthesized by applying the electrochemical anodization (ECA). The synthesis process was conducted at different voltages (10, 40, and 60) V in 1 h and using electrophoresis deposition (EPD) in doping zeolite. The MZTC was covered with the array ordered, smooth and optimum elongated nanotubes with 5.1 μm of the length, 120.3 nm of the inner diameter 14.5 nm of the wall thickness with pure titanium and crystalline titania as determined by FESEM/EDS, and XRD. The kinetic study by following Langmuir-Hinshelwood(L-H) model and pseudo first order, the significant constant rate was obtained at pH 11 which was 0.079 ppm/min, 0.75 cm2 of MZTC catalyst loading size achieved 0.076 ppm/min and 5 ppm of TCC initial concentration reached 0.162 ppm/min. The high-performance liquid chromatography (HPLC) analysis for mechanism study of TCC photocatalytic degradation revealed eleven intermediate products after the whole process of photocatalysis. In regard of toxicology assessment by the bacteria which is Photobacterium phosphoreum, the obtained concentration of TCC at minute 60 was less satisfied with remained 0.36 ppm of TCC was detected indicates that the concentration was above allowable level. Where the allowable level of TCC in stream is 0.1 ppm